THE USE OF PRONUNROID IN LEARNING ENGLISH TO IMPROVE PRONUNCIATION SKILLS - Ellisa Herawati; Arham Mauriyat (IKIP Siliwangi, 2022)
Pronunciation is the action or method of pronunciation of words; utterances, ways of speaking words, especially ways generally accepted or understood, and graphical representations of the way words are spoken, using phonetic symbols. In this journal the author wants to use supporting media as a tool to make pronunciation skills easier and can be done by anyone, whether in school or outside school, because pronunciation skills are very important in learning about foreign languages, pronunciation has become an indicator important for vocabulary and speaking. The author uses several sources from the internet such as journals, applications and videos. Due all elements are easier to navigate and indeed utilizing technological advancements in this era, The Writer hope that technological advances can facilitate the education world, especially in learning about the ability to pronounce in English. Keywords: English Pronunciation, Mobile-Assisted Language Learning, Pronunroid